The Authenticity of the Founding of Tito’s Yugoslavia as a Federation - Flere, Sergej (Sociološki pregled, 2019)
It is widely accepted that Tito’s Yugoslavia was institutionally founded at AVNOJ, namely the Second Session of the Anti-Fascist Council of National Liberation of Yugoslavia, held on November 29, 1943 in Bosnian woods. At the assembly, a Decree concerning the federal organization was to be adopted. The Decree contained principles of Yugoslavia’s future organization (six republics, along with the parity of republics and nationalities). Neither scholars nor politicians, in the former country and abroad, have questioned the veracity of the assertion that the Decree was adopted at this Session.The Decree was instrumental in the communist drive to impose a federation and communism, when confronted with pre-war politicians in the Transitional and Constitutional Assemblies, in 1945 and 1946. The communists were able to claim that federalism had already been instituted. Later, the Decree was widely invoked during Tito's Yugoslavia, both by those who advocated greater "states' rights" and by those claiming that Yugoslavia was already too decentralized.On closer inspection, it is more than questionable whether such constitutional Decree could have been adopted in such a situation. Many issues the decree governs were matters of contention and fnal decision making within AVNOJ afer the Second Session (and in 1945). Technicalities also point to the Decree not being adopted at that moment, but in an informal situation by the communist leaders at a later date, however, not later than February 1945. Nevertheless, the Decree widely functioned as a source of legitimacy and an instrument for setting certain limits in the political life of the former state.
Keywords: Anti-Fascist Council of National Liberation of Yugoslavia (AVNOJ); Josip Broz Tito; ehnicity; communism